Fondasi Rasional Kurikulum Modern Dan Relevansinya Dalam Konteks Pendidikan Kontemporer Perspektif Ralph W. Tyler - Tohari Tohari; Fajar Setiawan (Journal of Innovative and Creativity, 2025)
Ralph W. Tyler’s rational curriculum model has long served as a foundational pillar in educational planning, offering a systematic structure grounded in clarity, purpose, and measurability. However, in today’s rapidly evolving educational landscape—shaped by digital disruption, social complexity, and a growing call for learner-centered approaches—Tyler’s model invites critical reconsideration. This study explores the enduring relevance of Tyler’s curriculum framework within the context of 21st-century education, emphasizing its philosophical foundations, structural logic, and limitations when applied in humanistic and postmodern learning environments. Employing a qualitative, literature-based method, this paper critically analyzes Tyler’s core principles—educational objectives, learning experiences, content organization, and evaluation—and juxtaposes them with contemporary curricular discourses such as constructivism, critical pedagogy, and Understanding by Design. The findings reveal that while Tyler’s model retains practical value as an organizational scaffold, it requires significant epistemological renewal to remain responsive to today’s learners and societal needs. As a theoretical contribution, this paper proposes a Rational–Praxis Curriculum Design—a hybrid model that maintains the integrity of Tyler’s rationality while integrating reflective praxis and a more humane, contextual approach to learning. This model aspires to bridge the gap between structured educational planning and the lived realities of teaching and learning.